BATAS FASA STRUKTUR MESOSKOPIK SUPERKONDUKTOR HIBRID PB/AL - Liza Namigo, Elistia; Schildermans, Nele (Jurnal Spektra, 2014)
Investigation of the phase boundary of superconducting Pb/Al hybrid macroscopic and mesoscopic structures is conductedÂ and reported. The structures consists of 50 nm thin Al circular disk with 50 nm Pb disk deposited on top of it and 10 nm GeÂ deposited in between as insulation layer. Radius of the disk is 4 Î¼m for macroscopic and 1,5 Î¼m for mesoscopic structures.Â Deposition process was carried out with bi-layer lift-off electronic beam lithography technique. The measurements areÂ performed in a 3He bath cryostat with temperature range from below 1 K to less than 7.19 K (Tc of Pb). Current of 5Î¼A isÂ applied to the sample and the R(T) measurement is performed for constant magnetic field H. Measurements are done forÂ several values of magnetic field with a step of 0.1 mT. Field cooled measurements on macroscopic Al disk with diameter 4Â Î¼m and 1,5 Î¼m and 50 nm thickness were carried out for reference. Results indicates that Pb strongly screened the field of AlÂ for both macroscopic and mesoscopic samples with Little-Parks oscillation observed for mesoscopic disk. Tc values ofmacroscopic and mesoscopic samples show that superconductivity nucleation is strongly dependant on samplesâ boundaryÂ surface.Keywords: Coherence Length, Phase-Boundary, Little-Parks Oscillations.